Wires and nerve. Volume 1 - Meyer, Marissa; Holgate, Douglas; Gilpin, Stephen (2017)
When rogue packs of wolf-hybrid soldiers threaten the tenuous peace alliance between Earth and Luna, Iko, the android with a heart of (mechanized) gold, takes it upon herself to hunt down the soldiers' leader. She is soon working with a handsome royal guard who forces her to question everything she knows about love, loyalty, and her own humanity
Keywords: Cyborgs -- Comic books, strips, etc; Imaginary wars and battles -- Comic books, strips, etc; Young adult fiction